Simulation and Performance Analysis of a Dual GSM Band Rectifier Circuit for Ambient RF Energy Harvesting - Yusoff, Saiful Syazwan; Malik, Syed Abdul; Ibrahim, Taib (Applications of Modelling and Simulation, 2021)
In this article, an intelligent rectification circuit capable of collecting radio frequency (RF) from dual GSM bands for small DC power applications is proposed. The RF energy harvesting system (RFEH) is designed to gather RF energy at GSM 900 MHz (950 MHz band) and GSM 1800 MHz (1850 MHz band) carrier signals. The RFEH system comprises an impedance matching network (IMN) and a voltage multiplier circuit (double rectifier). Conventional IMNs are made up of passive components such as inductors and capacitors. However, these components degrade at high RF due to their material characteristic behaviour. The IMN based on distributed element or also known as stubbing configuration is presented to maximize the output DC power generated by the voltage multiplier circuit which boosts up the overall RFEH circuit performance. The circuit performance was analyzed with the Advanced Design System (ADS) simulation software to find the optimum RF power conversion efficiency of several input power levels. The propositioned RFEH circuit achieves utmost effectiveness for RF-DC conversion at 43.514% and 25.985% for the 950 MHz and 1850 MHz bands, respectively, for a low input RF power of -10 dBm with an optimum load of 25 kΩ. These results present a promising RFEH circuit network, making it a good candidate for low-level RF input power applications that allow wireless sensor network circuits or devices.